Motivasi Suami dan Paritas Mempengaruhi Kecemasan Ibu Hamil Menjelang Persalinan - Asriaty Dinopawe; Bazrul Makatita; Kharisma Lestina Alerbitu (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2021)
Background: Anxiety before delivery can cause the birth process to take a long time and bleeding occurs. Maternal anxiety is influenced by family support in this case husband and parents. Primarily pregnant women who get support from their families can reduce anxiety. Purpose: To determine the effect of the husband's motivation and parity on the anxiety of pregnant women before delivery. Methods: This study used a cross-sectional study design. The population and sample in this study were 32 pregnant women using the total sampling technique. The tool used for data collection is a questionnaire consisting of questions related to motivation, parity, and anxiety. Data analysis using univariate and bivariate with Fisher exact test. Results: The results showed that there was an influence between motivation and parity on anxiety before delivery (p = 0.001). Conclusion: Husband's motivation reduces anxiety in pregnant women before delivery and multiparous women have less anxiety than primiparous women. The role of the husband in motivating and providing strengthening for maternity mothers needs to be increased by pregnant women before delivery, especially for primiparous mothers, so that maternal anxiety can be minimized and childbirth can be normal without complications.AbstrakLatar Belakang: Kecemasan menjelang persalinan dapat menyebabkan proses kelahiran bayi berlangsung lama dan terjadi perdarahan. Kecemasan ibu bersalin dipengaruhi oleh dukungan keluarga dalam hal ini suami dan orang tua. Ibu hamil primi yang mendapatkan dukungan dari keluarga dapat mengurangi kecemasan. Tujuan: Mengetahui pengaruh motivasi suami dan paritas terhadap kecemasan ibu hamil menjelang persalinan. Metode: Studi ini menggunakan rancangan studi cross sectional. Populasi dan sampel dalam penelitian ini adalah ibu hamil yang berjumlah 32 orang dengan menggunakan teknik total sampling. Alat yang digunakan untuk pengumpulan data adalah kuesioner yang terdiri dari pertanyaan-pertanyaan terkait motivasi, paritas dan kecemasan. Analisis data menggunakan univariat dan bivariat dengan fisher ecaxt test. Hasil: Hasil penelitian diperoleh ada pengaruh antara motivasi dan paritas terhadap kecemasan menjelang persalinan (p= 0,001). Simpulan: Motivasi suami mengurangi kecemasan pada ibu hamil menjelang persalinan dan ibu multipara memiliki kecemasan yang kurang dibandingkan ibu primipara. The husband's role in motivating and providing strengthening for mothers facing childbirth needs to be increased, especially for primiparous mothers, so that maternal anxiety can be minimized and childbirth can be normal without complications.